Splintegrate - Christian, Deborah (Tor, 2019)
One of the many charms of planet Lyndir is the Between-World, home to the licensed entertainers of the Sa'adani Empire. There, at a palatial house of domination called Tryst, professional dominatrix Kes has become a celebrity attraction whose fame and exclusivity draws a rarified clientele. Her most devoted client is Janus, a major crime boss on Lyndir and elsewhere. But when a high-powered imperial authority decides she wants Janus out of the way, she identifies Kes as his greatest vulnerability. The seductive domina would never betray a client's trust, but a mortal threat to her Between-World sisters forces her cooperation with Janus's enemy. Altered against her will, she is turned into a brutal weapon by Splintegrate cloning technology. It will take help from some unlikely avenues and an enormous triumph of will for Kes to survive the government's machinations. . . and pursue the independence she's craved her entire life.